Geomagnetic Fields and Total Electron Content Variations at Eagle Station During Solar Storms of Solar Cycle 24 (Journal of Nepal Physical Society, 2024)
In this work, we analyzed variations in the Earth’s magnetic field components (D, H, and Z), interplanetary magnetic field (IMF-Bz), interplanetary electric field (IEF-Ey), and GPS-derived total electron content (TEC) during three solar storms observed over Eagle Station (64.7860°N, 141.1999°W) in Canada during Solar Cycle 24. The selected events include a moderate storm (25–27 October 2011), an intense storm (15–19 March, 2015), and a weak storm (6–10 May, 2018). The results indicate that solar storms caused notable disturbances in all components of the geomagnetic field, with the D, H, and Z components showing marked decreases during storm periods. These disturbances were accompanied by a corresponding increase in TEC. Additionally, the degree of geomagnetic variation was closely linked to the intensity of geomagnetic storms.